2010
DOI: 10.1002/art.27678
|View full text |Cite
|
Sign up to set email alerts
|

CCL17/thymus and activation–related chemokine in Churg‐Strauss syndrome

Abstract: Objective. Churg-Strauss syndrome (CSS) is a Th2-mediated systemic vasculitis characterized by eosinophilic infiltration, blood eosinophilia, and high IgE levels. CCL17/thymus and activation-regulated chemokine (TARC) is a chemokine responsible for the recruitment of Th2 cells. This study was undertaken to explore a possible role of CCL17/TARC in CSS.Methods. CCL17/TARC levels in serum from patients with active or inactive CSS, hypereosinophilic syndrome, systemic small-vessel vasculitis other than CSS, other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 27 publications
(29 reference statements)
0
59
0
4
Order By: Relevance
“…Although this biomarker needs diagnostic validation, it is likely to come into use in daily clinical practice. Recent studies have demonstrated elevated concentrations of proteins related to eosinophilia, particularly eotaxin-3, allowing to distinguish EGPA from other vasculitis or hyper-eosinophilia conditions [5]. Another marker of disease activity described in some studies is eosinophil cationic protein (ECP) [64].…”
Section: Blood Cells and Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this biomarker needs diagnostic validation, it is likely to come into use in daily clinical practice. Recent studies have demonstrated elevated concentrations of proteins related to eosinophilia, particularly eotaxin-3, allowing to distinguish EGPA from other vasculitis or hyper-eosinophilia conditions [5]. Another marker of disease activity described in some studies is eosinophil cationic protein (ECP) [64].…”
Section: Blood Cells and Biomarkersmentioning
confidence: 99%
“…Since anti-neutrophil cytoplasmic antibodies (ANCA) have been found in a proportion of patients, EGPA has subsequently been included in the spectrum of ANCA-associated vasculitis (AAV), along with GPA and microscopic polyangiitis (MPA) [4]. Several studies have elucidated the role of immune mechanisms, identifying genetic associations with HLA-DRB4 while recognizing new diagnostic and follow-up biomarkers (e.g., eotaxin-3) [5][6][7][8][9][10][11]. Finally, the treatment approach has improved through the use of immunosuppressive drugs and biological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Promising markers of the disease are those referring to activity and survival of eosinophils, like serum eosinophil cationic protein (Guilpain P et al, 2007), IL-5 (Tsukadaira A et al, 1999) or eotaxin-3 (CCL26), an eosinotactic chemokine mainly expressed on vascular endothelial cells and dermal fibroblasts (Polzer K et al, 2008). Recently, serum levels of TARC have been reported to be significantly elevated in CSS patients with active disease, and to correlate with the clinical course of the disease and with the absolute eosinophil counts, as well as with IgE levels (Dallos T et al, 2010). No confirmatory data are otherwise reported about the role of other eosinophil survival related molecules and interaction with the endothelium.…”
Section: Markers Of Diseasementioning
confidence: 99%
“…Given the expression profile of its receptors and the ability of CCL17/TARC to selectively induce migration of CD4+CD45RO+ T cells producing Th2 cytokines , it may be crucial for the specific recruitment and trafficking of Th2 cells, which are known to be activated in CSS. CCL17/TARC in the affected tissue of CSS patients is readily identified by immunohistochemical analysis, thus it may contribute to CSS pathogenesis by recruitment of Th2 cells into affected tissue (Dallos T et al, 2010).…”
Section: The Role Of T Cells 511 T Helper Cellsmentioning
confidence: 99%
“…Although this has not been investigated prospectively in this setting, evidence along this line has been produced for other diseases, namely Churg-Strauss syndrome and cutaneous T-cell lymphoma [79,80]. Measurement of serum TARC is reproducible and straightforward but is not performed in routine laboratories.…”
Section: Disease Biomarkersmentioning
confidence: 99%